Factors associated with a positive willingness to practise oral health care in the future amongst oral healthcare and nursing students. (6th June 2018) - Haresaku, S.; Monji, M.; Miyoshi, M.; Kubota, K.; Kuroki, M.; Aoki, H.; Yoshida, R.; Machishima, K.; Makino, M.; Naito, T.
Abstract: Objectives: The purpose of this study was to identify the weak points in the knowledge and attitudes of first‐year oral health care and nursing students towards oral health care and to identify the factors associated with their positive willingness to practise oral health care after becoming a health professional in order to develop oral healthcare curricula. Materials and methods: The subjects were 88 first‐year dental students (DSs), 64 dental hygiene students (DHSs) and 119 nursing students (NSs) enrolled in schools in Japan, as of April 2017. A questionnaire was distributed to subjects in each school to assess their knowledge and attitudes towards oral health care. Results: Less than half knew that oral health care was also provided in cancer hospitals, hospices, acute care hospitals, maternity wards and psychiatric wards. Only 46.2% knew that oral health care was effective in the prevention of aspiration pneumonia. The level of knowledge and attitudes in NSs regarding oral health care were likely to be lowest amongst the student groups. Only NSs' high interest towards oral health care was associated with their positive willingness to practise oral health care in the future although oral health students' high perceptions and interest regarding oral health care were associated with the willingness. Conclusion: This study showed oral healthcare and nursing students' weak points regarding their attitudes and knowledge of oral health care at early stages. Oral health academic staff and professionals should develop effective oral healthcare curricula for oral healthcare students and help nursing staff develop a collaborative nursing oral healthcare curriculum to motivate nursing students.